1989
DOI: 10.1096/fasebj.3.8.2721856
|View full text |Cite
|
Sign up to set email alerts
|

Anticachectin/tumor necrosis factor‐α antibodies attenuate development of cachexia in tumor models

Abstract: C57BL/6 mice bearing either a transplantable methylcholanthrene-induced sarcoma or Lewis lung adenocarcinoma were passively immunized every other day with a rabbit immunoglobulin fraction raised against murine cachectin/tumor necrosis factor-alpha. Mice bearing methylcholanthrene-induced sarcoma developed tumor-associated hypophagia that was attenuated by anticachectin immunoglobulin treatment. In the same tumor-bearing animals, anticachectin treatment also significantly reduced the extent of carcass protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
2
5

Year Published

1990
1990
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(93 citation statements)
references
References 0 publications
9
77
2
5
Order By: Relevance
“…Only a few murine tumor models have been reported to induce a cachexia-like syndrome. [12][13][14][15][16] Tumor cell-and host-produced cytokines such as IL-6, TNF-␣ and IFN-␥ are thought to play an important role in the catabolism and weight loss associated with several malignant and nonmalignant conditions. 10,11,[17][18][19] However, the specific contribution of human tumor cell-secreted IL-6 to body weight loss has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few murine tumor models have been reported to induce a cachexia-like syndrome. [12][13][14][15][16] Tumor cell-and host-produced cytokines such as IL-6, TNF-␣ and IFN-␥ are thought to play an important role in the catabolism and weight loss associated with several malignant and nonmalignant conditions. 10,11,[17][18][19] However, the specific contribution of human tumor cell-secreted IL-6 to body weight loss has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines such as interleukin-lbeta (IL-lb), interleukind (IL-6), and tumor necrosis factor-alpha (TNF-a) are upregulated in various animal cachexia models. Neutralization of these factors by genetic or pharmacological methods leads to attenuation of cachexia (Plata-Salaman, 1998;Plata-Salaman and Borkoski, 1994;Sherry et al, 1989;Vallieres and Rivest, 1997;Yasumoto et al, 1995). Finally, chronic infusion of IL-lp or TNF-cx causes anorexia, rapid weight loss, and catabolism of body protein stores, analogous to the state observed with chronic illness Plata-Salaman et al, 1996).…”
Section: A the Role Of Cytokinesmentioning
confidence: 99%
“…Weight loss produced by TNF is typified by a marked anorexia, and the decrease in food and water intake is directly proportional to the decrease in body weight . However, anti-TNF antisera has been shown to delay, but not fully protect against the decrease in food intake in sarcomabearing mice (Sherry et al, 1989), suggesting that other factors in addition to TNF may be responsible for the anorexia in tumour-bearing animals. It has been suggested that TNF produces an effect on lipid metabolism through an inhibition of the enzyme lipoprotein lipase (Beutler et al, 1985b), and thus depletion of host lipids would be mediated through a different mechanism from the action of the direct catabolic factors mentioned above.…”
Section: Mechanism Of Cachexiamentioning
confidence: 99%
“…Attempts to reverse the cachexia in tumour-bearing animals with anti-TNF antibodies have produced equivocal results (Sherry et al, 1989). Unfortunately, both models used by these workers had a higher tumour burden, and measurements were made at the time of death.…”
Section: Mechanism Of Cachexiamentioning
confidence: 99%